FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK SUSU BUBUK PERTUMBUHAN - Suprapto, Dedy Aguspriandono; Nurmalina, Rita; Fahmi, Idqan (Jurnal Ilmu Keluarga dan Konsumen, 2014)
The objectives of this study were to examine the factors of product atribute that affecting consumers in purchase decision making of growth formula for their toddlers. The study was conducted in Jakarta during December 2013 until Februari 2014 and involved 140 respondents of growth formula consumers. Data were analyzed by using logistic regression test. The results indicated that the main factors that influenced the consumers in purchase decision making of growth formula for their toddlers were compositional and nutritional value, suitability of milk that consume by their toddler, and product safety. Marketing strategy which can do by producer is educating consumer about the important composition and nutritional value contained in growth formula, reformulating ingredient contained in growth formula so that resulting a positive effect for a toddler who consume it, following requirement and licensing Ministry of Health and The National Agency of Drugs and Food Control (BPOM) to ensure that products which are available in market are the safe products.